2006
DOI: 10.1063/1.2185259
|View full text |Cite
|
Sign up to set email alerts
|

Microscopic interfacial structures and magnetic properties of ultrathin Co∕Si(111) films

Abstract: The relation between magnetic properties and microscopic structure for a metal/semiconductor system is described. Cobalt films on a CoSi interface possess an in-plane easy axis of magnetization as the result of magnetocrystalline anisotropy of the Co∕CoSi interface. On a Si(111)-7×7 surface, direct evidence for the formation of CoSi2 compounds at the interface was found by the appearance of doubled spot defects in scanning tunneling microscopic images. The interfacial effects cause the easy axis of magnetizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
31
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 15 publications
2
31
1
Order By: Relevance
“…This behavior shows that the Co adatoms all contribute to the magnetization. No nonmagnetic layer at the interface was detected as compared to the metal/ semiconductor systems [24,25]. As the Co thickness increases above 8 nm, the slope of the Kerr intensity versus Co thickness plot decreases.…”
Section: Resultsmentioning
confidence: 90%
“…This behavior shows that the Co adatoms all contribute to the magnetization. No nonmagnetic layer at the interface was detected as compared to the metal/ semiconductor systems [24,25]. As the Co thickness increases above 8 nm, the slope of the Kerr intensity versus Co thickness plot decreases.…”
Section: Resultsmentioning
confidence: 90%
“…The background pressure of the UHV chamber was lower than 3×10 -10 Torr. The various components are described in detailed elsewhere [4,13]. The Ge(111) surface was cleaned by means of Ar + ion bombardment and subsequent annealing cycles until a well-ordered c(2×8) pattern was observed by LEED and no chemical impurity on the substrate surface was detected by AES.…”
Section: Methodsmentioning
confidence: 99%
“…In recent years magnetic films on semiconductor substrates have drawn much attention because of their interesting science and tremendous applications [1][2][3][4]. A great deal of literature focused on the influences of the physical properties of the films by the interfaces [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The most inter esting experimental investigations of the structural and magnetic properties have been reported for Fe/Si [7⎯11] and Co/Si [10][11][12][13][14][15][16][17][18][19] thin film systems. Analysis of the available data showed that the antiferromagnetic exchange between iron layers in Fe/Si/Fe systems was observed for silicon layer thicknesses within 1.4-1.7 and 1.4-2.2 nm (see, e.g., [20,21]).…”
mentioning
confidence: 99%